Mandibular third molar and angle of mandible fractures: an unsolved clinical dilemma - Rajandram, R.K; Nabil, S; Shareif, M.S; Ishak, I; Marhazlinda, J; Nordin, R; Nazimi, A.J (Universiti Kebangsaan Malaysia, 2013)
The purpose of this study was to investigate the relationship between partially erupted impacted mandibular third and the risk for angle of mandible fracture. We designed a retrospective cohort study composed of patients who presented with mandible fractures. The predictor variables were the presence and angulation of the partially erupted impacted mandibular third molar and the distance between the apices of the mandibular third molar and the inferior border of the mandible. The outcome variable was the presence or absence of an angle fracture. Patients with a partially erupted impacted mandibular third molars had a 3.3 times greater chance of an angle fracture than patients without mandibular third molars (p<001). No significant association was found between the distance of the apices and angulation of the mandibular third molars to the inferior border of the mandible with angle of mandible fractures. Our findings highlight the need for enforcement of proper protective gear in young individuals who are at high risk for facial trauma.